REVERSE REALIZATION OF PITCH CURVE ON CONJUGATE CAM WITH HIGH SPEED BEATING-UP - QIU HaiFei (Jixie qiangdu)
In order to meet the requirements of beating up technology on conjugate cam,a modified trapezoid acceleration law is used to construct motion equation of reed by segment. The reverse design program of conjugate cam is developed by MATLAB software,and precise reverse design of pitch curve on main and auxiliary cam are realized which on the basis of reconstructing law of beating-up motion. Besides,shape change of the pitch curve is analyzed by combining swing arm angle Φand center distance L. The results of reverse design show that pressure angle α at each point on the curve can meet requirements of mechanical transmission characteristics. The reasonable values of basic circle radius and roller are determined through calculating radial direction r0 and radius of curvature ρ0 of the curve point by point. The results provides a technical idea for reverse and design innovation of the conjugate cam on beating-up mechanism.